Analysis of PPE Use with Occupational Disease Risk Control: Analytical Study of Ppe Use at The Sudiang Raya Public Health Center, Biringkanaya District, Makassar City - Harlina; Firman Alamsyah R; Andi Alim; Asriani Minarti S (Universitas Nahdlatul Ulama Surabaya, 2023)
The use of PPE is closely related to occupational diseases caused by work factors or diseases acquired while doing work and occur over a long period. This study aimed to determine the relationship between Knowledge, Compliance with the use of PPE, Availability of PPE, Implementation of Standard Operating Procedures (SOP) for the use of PPE and PPE Implementation Policy with Occupational Disease Risk Control. This research is quantitative with an analytic survey approach using a cross-sectional study method. The population in this study were all health workers with a total sample of 28; the sample was all nurses/doctors and midwives. Based on the square or comparative test results to determine the relationship between occupational disease risk control. The results showed that there was no relationship between knowledge (P=0.608), there was a relationship between the availability of Personal Protective Equipment (PPE) (P=0.002), Standard Operating Procedures (SOP) (P=0.004), Compliance with using Personal Protective Equipment (PPE) (P = 0.000). There is no relationship between policy (P = 0.0604) and controlling the risk of occupational diseases. Interventions are needed to ensure the availability of personal protective equipment (PPE) such as masks, and protective goggles, adherence to the use of self- protection equipment (PPE), and the implementation of Standard Operating Procedures (SOP) in each unit requires complete control so that the Standard Operating Procedures (SOP) are implemented, and adherence to the use of Personal Protective Equipment (PPE) requires awareness/not negligence in using Personal Protective Equipment (PPE) when serving patients to avoid risks occupational illness.